Rancang Bangun Aplikasi Kraepelin Test Berbasis Web Menggunakan Metode Bubble Sort - Harmein Pane; Fauziah -; Nurhayati - (Universitas Widyagama Malang, 2020)
Psychological testing has now become an important enough part of life to be able to understand and recognize one's potential and personality. One of the instruments used by psychologists is Kraepelin test. Kraepelin test is part of a psychological test that measures speed, accuracy, constancy, and endurance at work. The scoring process is currently done manually, so it requires time, calculation process and high accuracy, for this research makes a website-based application with the aim to facilitate scoring so that it can anticipate misperceptions about the results of other people's tests because scoring errors are done manually. Kraepelin test in this application uses the UI version which amounts to 40 question lines referring to the standard standards of the Kraepelin Test norm. To maintain the rigidity of the problem, the Bubble Sort method is used. Psychology Expert Test obtained the percentage of suitability between the application with the manual, namely: Panker (Speed) 100%, Tianker (Accuracy) 100%, Janker (Constancy) 100% and Hanker (Endurance) 100%.